Attacking agility actions: match play contextual applications with coaching and technique guidelines - Dos'Santos, T.; McBurnie, A.; Thomas, C.; Jones, P. A.; Harper, D. (Strength and Conditioning Journal, 2022)
Attacking agility actions, such as side steps, shuffle steps, crossover cutting, split steps, spins, decelerations, and sharp turns, are important maneuvers in invasion team sports, often linked with decisive match winning moments. Generally, the aims of these actions are to (a) evade and create separation from an opponent, (b) generate high exit velocities and momentums, or (c) facilitate a sharp redirection. However, these actions are also inciting movements associated with lower-limb injury. Given the importance of agility actions for sports performance and potential injury risk, in this review, we discuss the importance and contextual applications of attacking agility actions, while providing coaching and technique guidelines to best optimize the performance-injury risk conflict.